2003
DOI: 10.1093/nar/gkg664
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms (SNPs) that map to gaps in the human SNP map

Abstract: An international effort is underway to generate a comprehensive haplotype map (HapMap) of the human genome represented by an estimated 300,000 to 1 million 'tag' single nucleotide polymorphisms (SNPs). Our analysis indicates that the current human SNP map is not sufficiently dense to support the HapMap project. For example, 24.6% of the genome currently lacks SNPs at the minimal density and spacing that would be required to construct even a conservative tag SNP map containing 300,000 SNPs. In an effort to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…another previous study, we observed a validation rate of 29/30 (97%) for SNPs discovered with our pipeline (Table 4; Tsui et al 2003). Therefore, with the exception of the single-base pair INDELs discussed above, our computational pipeline yields accurate predictions for the major polymorphism classes identified in our study.…”
Section: Validation Studiessupporting
confidence: 71%
See 2 more Smart Citations
“…another previous study, we observed a validation rate of 29/30 (97%) for SNPs discovered with our pipeline (Table 4; Tsui et al 2003). Therefore, with the exception of the single-base pair INDELs discussed above, our computational pipeline yields accurate predictions for the major polymorphism classes identified in our study.…”
Section: Validation Studiessupporting
confidence: 71%
“…This pipeline has been used previously to identify SNPs (Tsui et al 2003) and transposon insertions (Bennett et al 2004). Traces obtained from TSC or NCBI first were trimmed to remove vector sequences using the VecScreen system from NCBI.…”
Section: Indel Discovery Pipelinementioning
confidence: 99%
See 1 more Smart Citation
“…Our computational pipeline simultaneously detects both INDELs and SNPs from ABI trace data, and has high levels of accuracy with both classes of variation (Tsui et al 2003;Mills et al 2006; please see Methods). We determined that the genome-wide ratio of INDELs to SNPs was 0.19 (i.e., 1 INDEL for every 5.3 SNPs) (Supplemental Table 7).…”
Section: Evidence For Strong Purifying Selection On Coding Indelsmentioning
confidence: 99%
“…Traces were processed and compared to the hg18 build of the human genome using quality scores to guide the analysis, as described previously (Mills et al 2006). INDELs were defined as insertions or deletions in the 1-bp to 10,000-bp size range that could be detected by comparing ABI traces to the reference genome as outlined previously (Tsui et al 2003;Bennett et al 2004;Mills et al 2006). All variants were entered into a Perl dbfile hash module to identify redundancies, and then into a MySQL database, which was used to store and analyze the data.…”
Section: Identification and Analysis Of Indels From Ncbi Trace Datamentioning
confidence: 99%